South-South Paradiplomacy: A Channelling Mechanism of Denpasar-Mossel Bay Sister-City Cooperation - Isti Nur Rahmahwati; Jevons Kollie Kawala (Universitas Muhammadiyah Yogyakarta, 2025)
The practice of paradiplomacy in the Global South countries is currently on the rise. While prior studies have predominantly focused on Global North paradiplomacy, this paper demonstrates how legal regimes structurally channel paradiplomacy yet remain resilient in digital formats, using a case study of Denpasar-Mossel Bay sister city cooperation. It was analyzed as a contemporary manifestation of South-South cooperation rooted in the historical ‘Bandung Spirit’ but adapted to the modern imperatives of local development. This paper refines Lecours’ three-layered model of paradiplomacy by situating it within a Global South regulatory context, employing qualitative analysis of a case study and discourse. The findings revealed that Denpasar-Mossel Bay sister city cooperation is a pragmatic and resilient form of apolitical paradiplomacy, strategically focused on economic and cultural-technical objectives while deliberately avoiding political dimensions. This channeling of sub-national ambition is a direct consequence of the national regulatory framework. The case exhibits a remarkable capacity for adaptation, particularly through the adoption of digital methods during the COVID-19 pandemic, which helped sustain the relationship and ultimately led to its renewal. The paper concluded that South-South paradiplomacy represents a viable, cost-effective model for mutual development, knowledge exchange, and a democratized form of international engagement for sub-national actors in developing countries.